The potential of microfluidic cell analysis in CAR T cell therapy manufacturing - Nikoniuk, Aleksandra; Lilova, Koki; Thomas, Michael; Szita, Nicolas (Frontiers in Bioengineering and Biotechnology, 2025)
Despite significant success in treating hematological cancers, Chimeric Antigen Receptor (CAR) T cell therapies must overcome several challenges to become accessible to a wide patient population. With the high cost of treatment stemming partly from the complexity of the manufacturing process, there is a need for radical innovation in the ways those therapies are made. A crucial aspect of the manufacturing process is quality control (QC), responsible for monitoring the quality of the drug product. The use of microfluidic technology, in which microchannels are designed and fabricated to achieve high control of liquids, can increase sensitivity, lower the Limit of Detection (LoD), and improve time-to-result of analytical assays. This review examines how recently developed microfluidic devices for T cell analysis fit the requirements of QC testing in CAR T cell manufacturing. A particular focus is on cell counting, cell phenotyping, and cytotoxicity assessments, where a range of microfluidic approaches have been taken to deliver reliable analytical assays. The review not only highlights current limitations of microfluidic devices that hinder their implementation in manufacturing, but also their potential to expand on current QC testing.